Kegiatan Membersihkan Masjid Al Huda dalam Rangka Menjaga Kebersihan Rumah Ibadah di Daerah Jambangan Surabaya - Roidatus Shofiyah; Soepardi Redjo; Taufan Hamim Fitroni (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Mosque is a holy place of worship for Muslims used for prayer, dhikr, studying religion, and other religious activities. Therefore, the cleanliness of the mosque must be maintained properly to create a comfortable, solemn, and healthy environment for the congregation. If the mosque is left for a long time, dirt will arise that must be cleaned. The purpose of this PKM is to maintain the cleanliness of the mosque for a certain time. The focus of this service is to maintain the cleanliness of the mosque. A clean mosque must still be kept clean so that the community is comfortable and peaceful in performing worship. This activity was carried out at the Al Huda mosque, Jl Karah Agung V No. 2A Karah Jambangan Surabaya on March 22, 2025 from 8 to 10 WIB with 10 participants. The PKM method uses community empowerment, where service participants directly participate in the activity. As a result, with this PKM, the mosque is kept clean.